Influence of education level on the effectiveness of pain neuroscience education: A secondary analysis of a randomized controlled trial. (February 2022) - Bilterys, Thomas; Kregel, Jeroen; Nijs, Jo; Meeus, Mira; Danneels, Lieven; Cagnie, Barbara; Van Looveren, Eveline; Malfliet, Anneleen
Abstract: Background: Current evidence supports the use of pain neuroscience education (PNE) in several chronic pain populations. However, the effects of PNE at group level are rather small and little is known about the influence of personal factors (e.g. level of education [LoE]). Objective: To examine whether the effectiveness of PNE differs in chronic spinal pain (CSP) patients with high LOE (at least a Bachelor's degree) versus lower educated patients. Method: A total of 120 Belgian CSP patients were randomly assigned to the experimental (PNE) or control group (biomedical-focused neck/back school). Participants within each group were further subcategorized based on highest achieved LoE. ANOVA and Bonferroni post-hoc analyses were used to evaluate differences in effectiveness of the interventions between higher and lower educated participants. Results: No differences between higher and lower educated participants were identified for pain-related disability. Significant interactions (P < .05) were found for kinesiophobia and several illness perceptions components. Bonferroni post-hoc analysis revealed a significant improvement in kinesiophobia (P < .001 and P < .002, medium effect sizes) and perceived negative consequences (P < .001 and P < .008, small effect sizes) in the PNE groups. Only the higher education PNE group showed a significant improvement in perceived illness cyclicity (P = .003, small effect size). Post-treatment kinesiophobia was significant lower in the higher educated PNE group compared to the higher educated control group (p < .001). Conclusion: Overall, the exploratory findings suggest no clinical meaningful differences in effectiveness of PNE between higher and lower educated people. PNE is effective in improving kinesiophobia and several aspects of illness perceptions regardless of LoE. Highlights: There are no clinical meaningful differences in PNE effect between higher and lower educated people. Kinesiophobia and several illness perceptions improved after only 3 PNE sessions. Two general and one face-to-face PNE session is enough to get beneficial effects.